Evaluating the potential of mosque institution in contributing to the Disaster risk reduction (Ddr) system - Asif, Nayeem; Utaberta, Nangkula; Mydin, Md Azree Othuman (INSInet Publication, 2016)
The institution of mosque acted as the center of activity of Muslim communities for centuries. During the early days of Islam, administrative, educational, social, financial, and judicial activities were conducted centering the mosque. Up until now, mosque is one of the major establishment within a Muslim community in countries with Muslim majority as well as countries where Muslims are minority. It is almost inevitable that every Muslim community would have at least one mosque within the locality. For most of the cases in Muslim major countries, there are more than one mosque to be found in any locality. These institutions are mostly use for prayer, meditation and recitation purposes. But there are so many potentials to utilize these existing infrastructures as center for community development by extending the scope of activities with the participation of the community people. This paper aims to explore the possibilities of utilizing mosque as disaster management centers among Muslim communities.